STRATEGIES OF MADRASAH DEVELOPMENT TO IMPROVE EDUCATIONAL QUALITY - Elice, Deti; Pahrudin, Agus; Akmansyah, Muhammad; Patimah, Siti; Koderi, Koderi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Madrasah need to develop a development strategy into a quality Islamic educational institution so that madrasah are able to adjust to the demands of national education standards. This study aims to identify and analyze madrasah development strategies in improving the quality of education. This type of research is phenomology with a qualitative level of exploration. Purposive sampling of data was taken by the head of the madrasah and his deputy, teachers, and students. Data taken through observation and interviews whose results were analyzed inductively. The results of the study found madrasah development strategies, namely carrying out autonomy, optimizing community / parent participation, utilizing human resources owned, open and cooperative, responsibility and high performance, guidance from central and regional religious ministries, transparency, socialization of development concepts, and careful planning. The conclusion of the research is that the madrasah development strategy can improve the quality of education in MTs Negeri 1 Bandar Lampung better.